2007
DOI: 10.1111/j.1530-0277.2006.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on Hypothalamic Opioid Peptides, Enkephalin, and Dynorphin: Relationship With Circulating Triglycerides

Abstract: Background: Recent evidence has demonstrated that ethanol intake can stimulate the expression and production of the feeding-stimulatory peptide, galanin (GAL), in the hypothalamic paraventricular nucleus (PVN), and that PVN injection of this peptide, in turn, can increase the consumption of ethanol. To test the hypothesis that other feeding-related systems are involved in ethanol intake, this study examined the effect of ethanol on the hypothalamic opioid peptides, enkephalin (ENK), and dynorphin (DYN).Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 71 publications
7
83
1
Order By: Relevance
“…While earlier studies of endogenous opioids in whole hypothalamus yielded mixed results, ENK mRNA in the PVN was shown to be significantly stimulated after 24 hours by acute intragastric infusion of 30% ethanol [60], while unaffected by intake of 5% ethanol [61]. In a recent report [62], a strong, stimulatory effect of ethanol on PVN opioids has been described. Rats voluntarily drinking 9% ethanol (1.0-2.5 g/kg/day) show a significant increase in expression of both ENK and DYN in the PVN, similar to that seen with GAL.…”
Section: Relation Of Opioid Peptides To Alcohol Intakementioning
confidence: 90%
See 1 more Smart Citation
“…While earlier studies of endogenous opioids in whole hypothalamus yielded mixed results, ENK mRNA in the PVN was shown to be significantly stimulated after 24 hours by acute intragastric infusion of 30% ethanol [60], while unaffected by intake of 5% ethanol [61]. In a recent report [62], a strong, stimulatory effect of ethanol on PVN opioids has been described. Rats voluntarily drinking 9% ethanol (1.0-2.5 g/kg/day) show a significant increase in expression of both ENK and DYN in the PVN, similar to that seen with GAL.…”
Section: Relation Of Opioid Peptides To Alcohol Intakementioning
confidence: 90%
“…There is evidence that ethanol like dietary fat can increase circulating levels of TG [35,62,63]. The injection as well as consumption of ethanol in rats consistently increases circulating levels of TG, together with blood levels of alcohol [62].…”
Section: Relation Of Opioid Peptides To Alcohol Intakementioning
confidence: 99%
“…Enkephalin and dynorphin concentrations along with galanin, were found to be increased in the PVN with injection and consumption of alcohol (Chang et al, 2007). Like galanin, both of these endogenous opioids increase food intake.…”
Section: Development Of Alcohol Dependence: the Role Of Feeding Nutrmentioning
confidence: 97%
“…They found that in rats trained to prefer alcohol over water for many weeks, microinjection of this 29-30 amino acid peptide into the third ventricle near the paraventricular nucleus (PVN) (Lewis et al) or in the nucleus itself (Rada, Avena, Leibowitz, & Hoebel, 2004) increased alcohol intake. Furthermore, it has been recently observed that administration of alcohol increases galanin expression in the hypothalamus (Chang et al, 2007). In rats that had been consuming alcohol for 6 or more weeks, galanin did not increase the consumption of their chow diet.…”
Section: Development Of Alcohol Dependence: the Role Of Feeding Nutrmentioning
confidence: 99%
“…Besides, levels of orexin mRNA (Morgansterm et al et al, 2010) were reduced and levels of opioid encephalin and galanin were increased (Chang et al, 2007 by chronic exposure to ethanol.…”
Section: Introductionmentioning
confidence: 99%